Identification and characterization of circRNAs from different body color leopard coral grouper (Plectropomus leopardus) - Hao, Ruijuan; Zhu, Xiaowen; Tian, Changxu; Huang, Yang; Li, Guangli; Zhu, Chunhua (Frontiers in Marine Science, 2023)
Circular RNAs (circRNAs) play key roles in several biological processes in animals and their regulatory mechanism in body color formation or pigmentation in fish remains unclear. Here, circRNAs from black and red individuals of Plectropomus leopardus were identified to clarify the mechanism of circRNAs and the competing endogenous RNA (ceRNA) network (circRNA-microRNA (miRNA)-messenger RNA (mRNA)) in body color formation. We detected a total of 1,424 novel circRNAs. Expression analysis of circRNAs in black vs. red P. leopardus revealed 24 differentially expressed circRNAs (DECs), and 11 and 13 of these DECs were up-regulated and down-regulated in red individuals relative to black individuals, respectively (P<0.05 and |log2 Fold Change (FC)|>1). We identified a total of 19 significant miRNA-circRNA-mRNA ceRNA networks through the analysis of DECs, differentially expressed miRNAs (DEMs) and differentially expressed genes (DEGs). Pathway enrichment analyses of the DEGs involved in the ceRNA network revealed that they were mainly involved in melanin metabolism and immune response. Our findings showed the possibility of the regulatory functions of circRNAs and the corresponding ceRNA network in the body color formation process and will aid the breeding selection process of P. leopardus.